2020
DOI: 10.3390/s21010013
|View full text |Cite
|
Sign up to set email alerts
|

Amine Detection Using Organic Field Effect Transistor Gas Sensors

Abstract: Low power gas sensors with high sensitivity and selectivity are desired for many practical applications. Devices based on organic field effect transistors are promising because they can be fabricated at modest cost and are low power devices. Organic field effect transistors fabricated in bottom-gate bottom-contact configuration using the organic semiconductor [2,5-(2-octyldodecyl)-3,6-diketopyrrolopyrrole-alt-5,5-(2,5-di(thien-2-yl)thieno] [3,2-b]thiophene) (DPP-T-TT) were systematically investigated to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…166 While OFETs are of interest for applications as food sensors, these devices can suffer from high driving voltages, therefore, the devices considered for BA sensors should require low voltages such that a common battery can power them. 149,166,167…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…166 While OFETs are of interest for applications as food sensors, these devices can suffer from high driving voltages, therefore, the devices considered for BA sensors should require low voltages such that a common battery can power them. 149,166,167…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…For transistors, the potential for commercialization depends on the device design, where organic field effect transistors (OFETs), for example, have many components to consider and would be more challenging to mass manufacture, but have proven to be highly sensitive and have low LODs. 139,149,150 The electrochemical sensors covered here are summarized in Table 3.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, limited research has been reported on MOF-based OFET gas sensors. 167,171,[174][175][176] Recently, Yuvraj et al 177 reported a novel and highly sensitive and selective OFET-based transducer for NO 2 gas sensing. They designed an OFET platform ] n an isostructural to uorinated MOF combined with an organic semiconductor of PDVT-10 (as shown in Fig.…”
Section: Nanoscale Advances Reviewmentioning
confidence: 99%